1980
DOI: 10.1111/j.1346-8138.1980.tb01941.x
|View full text |Cite
|
Sign up to set email alerts
|

Organ Culture of Adult Human Skin

Abstract: Proliferation and differentiation of the epidermis in organ culture of adult human skin by the sponge matrix method were studied histologically and autoradiographically, and the following results were obtained: 1) On the first day of culture, mitotic figures were already observable in the epidermis. The outgrowth of epidermal cells at the margins of the explants started. On the second day, there was transformation to a zone that will be referred to as the newly formed stratum corneum in the upper epidermis. 2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1981
1981
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…In contrast with these results, other investigators have reported that triamcinolone acetonide does not alter the pattern of differentiation proteins, including keratohyalin granule related protein and cell enveloping proteins (19). Yasuno et al found a slight decrease in epidermal growth and differentiation in organ cultures of adult human skin in the presence of dexamethasone (20). It thus remains difficult to draw valid conclusions from the literature about the effects of corticosteroids on keratinocyte differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast with these results, other investigators have reported that triamcinolone acetonide does not alter the pattern of differentiation proteins, including keratohyalin granule related protein and cell enveloping proteins (19). Yasuno et al found a slight decrease in epidermal growth and differentiation in organ cultures of adult human skin in the presence of dexamethasone (20). It thus remains difficult to draw valid conclusions from the literature about the effects of corticosteroids on keratinocyte differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported the effect of corticosteroid in producing a long-term maintenance of adult human skin in organ culture (11). In our present experiments, the culture temperature was shifted from 37°C to 32°C in an attempt to prolong the survival of cultured skin.…”
Section: Introductionmentioning
confidence: 87%
“…The suggested readings show the number of publications produced in 1975 on the topic of in situ hybridization or immunohistochemistry; note that there were eight such papers [1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] . Compare this to the list of publications produced in 1980 on in situ hybridization or immunohistochemistry; note that there were 34 [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] . These references are included to give homage to the pioneers in these two fields.…”
mentioning
confidence: 99%